FEATURES OF DENTAL STATUS AND SOME MICROBIOLOGICAL PARAMETERS OF THE ORAL CAVITY OF YOUNG MEN. - Y.Y. Vodoriz; N.M. Ilenko; N.V. Ilenko; T.O. Petrushanko (Український стоматологічний альманах)
Normal oral microflora plays an important role in the protection of human organism from disease. Oral cavity can be attributed to one of the ideal habitat for living organisms of the human body. This habitat is subdivided into several subbiotops considering the anatomical structure and other characteristics of parts of the oral cavity such as gingival sulcus, gingival and periodontal pockets. The species composition of subbiotops` microflora directly depends on the protection of local and general factors. Every person`s oral cavity, besides its natural inhabitants (flora presented with lacto-and bifidobacterias) is presented with opportunistic and pathogenic microorganisms. Violation of quantitative relationships between normal and opportunistic flora leads to dysbiotic states and to decreasing of laktoand bifidobacterias ammount and growing of opportunistic microorganisms.